PENTINGNYA BIMBINGAN KLASIKAL DALAM PENGEMBANGAN ANAK DI PANTI ASUHAN MITRA - Welly , Putri; Hidayani Syam; Nutria Desi (CV. ADIBA AISHA AMIRA, 2024)
Classical Guidance has an important role in the development of children in partner orphanages. In this environment, Classical Guidance not only provides formal education, but also offers the emotional, social and psychological support necessary for the holistic growth of the children living there. This article explains the importance of Classical Guidance as an important foundation in shaping the potential of children in partner orphanages. The main focus is on the role of teachers or counselors in providing in-depth and Comprehensive Guidance for childrens personal development, and how this affects their lives in the future.